Outcomes of thoracic endovascular aortic repair in thoracic aortic aneurysm and penetrating aortic ulcer using the Conformable Gore TAG within and outside the instructions for use - Meisenbacher, Katrin; Hagedorn, Matthias; Grond-Ginsbach, Caspar; Kronsteiner, Dorothea; Böckler, Dittmar; Bischoff, Moritz (Vascular, 2021)
Objective - To describe the outcome of thoracic endovascular aortic repair (TEVAR) in thoracic aortic aneurysm and penetrating aortic ulcer with respect to instructions for use status. - Methods - Between October 2009 and September 2017, a total of 532 patients underwent TEVAR; of which 195 have been treated using the Conformable GORE® TAG® thoracic endoprosthesis (CTAG). Fifty-six patients of this cohort underwent TEVAR for thoracic aortic aneurysm/penetrating aortic ulcer using the CTAG. Depending on the preoperative computed tomography angiography findings, patients were classified as inside or outside the device’s instructions for use. All inside instruction for use patients underwent postoperative reclassification regarding the instructions for use status. Study endpoints included TEVAR-related reintervention, exclusion of the pathology (endoleak type I/III), TEVAR-related mortality, and graft-related serious adverse events. The median duration of follow-up was 29.7 months (range: 0-109.4 months). - Results - Of the 56 patients, 17 were primarily classified as outside instruction for use, and in additional 13 patients, TEVAR was performed outside instruction for use, leading to 30 outside instruction for use patients (53.6%). Twenty-six patients (46.4%) were treated inside instruction for use. Reintervention-free survival was lower in outside instruction for use patients (P = 0.016) with a hazard ratio of 9.74 (confidence interval 1.2-80.2; P = 0.034) for TEVAR-related reintervention. With respect to endoleak type I/III, relevant difference was detected between inside/outside instruction for use status (P = 0.012). The serious adverse event rate was 30.4%, mainly in outside instruction for use patients (P = 0.004). Logistic regression analysis indicated an association between graft-related serious adverse event/instructions for use status (odds ratio 6.11; confidence interval 1.6-30.06; P = 0.012). In-hospital death was seen more frequently in outside instruction for use patients (P = 0.12) as was procedure-related death (log-rank test: P = 0.21). - Conclusion - TEVAR for thoracic aortic aneurysm/penetrating aortic ulcer is frequently performed outside instruction for use despite preoperative inside instruction for use eligibility, leading to important consequences for technical/clinical outcome. Instructions for use adherence in TEVAR should be of interest for further large-scale studies.